Labor induction information leaflets-Do women receive evidence-based information about the benefits and harms of labor induction? - Peter von Dadelszen; Peter von Dadelszen; Susan Tohill; Julie Wade; Jennifer A. Hutcheon; Janet Scott; Marcus Green; James G. Thornton; Laura A. Magee; Laura A. Magee; the WILL Pilot Trial Study Group (Frontiers Media S.A., 2022)
ObjectivesTo determine the extent to which a sample of NHS labor induction leaflets reflects evidence on labor induction.SettingAudit of labor induction patient information leaflets-local from WILL trial (When to Induce Labor to Limit risk in pregnancy hypertension) internal pilot sites or national-level available online.MethodsDescriptive analysis [n = 21 leaflets, 19 (one shared) in 20 WILL internal pilot sites and 2 NHS online] according to NHS "Protocol on the Production of Patient Information" criteria: general information (including indications), why and how induction is offered (including success and alternatives), and potential benefits and harms.ResultsAll leaflets described an induction indication. Most leaflets (n = 18) mentioned induction location and 16 the potential for delays due to delivery suite workloads and competing clinical priorities. While 19 leaflets discussed membrane sweeping (17 as an induction alternative), only 4 leaflets mentioned balloon catheter as another mechanical method. Induction success (onset of active labor) was presented by a minority of leaflets (n = 7, 33%), as "frequent" or in the "majority", with "rare" or "occasional" failures. Benefits, harms and outcomes following induction were not compared with expectant care, but rather with spontaneous labor, such as for pain (n = 14, with nine stating more pain with induction). Potential benefits of induction were seldom described [n = 7; including avoiding stillbirth (n = 4)], but deemed to be likely. No leaflet stated vaginal birth was more likely following induction, but most stated Cesarean was not increased (n = 12); one leaflet stated that Cesarean risks were increased following induction. Women's satisfaction was rarely presented (n = 2).ConclusionInformation provided to pregnant women regarding labor induction could be improved to better reflect women's choice between induction and expectant care, and the evidence upon which treatment recommendations are based. A multiple stakeholder-involved and evidence-informed process to update guidance is required.